2019
DOI: 10.2478/eas-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Sukuma Loanwords in the Western Dialects of Datooga (Taturu) and its Dialectological Implications

Abstract: The exchange of linguistic materials between languages which come into contact is indeed reciprocal. The previous accounts of the outcome of contact between Datooga and Sukuma was skewed towards impact of Datooga on Sukuma. Based on ethnolinguistic vitality approach, the Datooga tend to reveal solidarity-related social identity by acquiring their language as a mother tongue. They also reveal prestige-related social identity by acquiring Sukuma language which is the prestigious lingua franca of the Itumba area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Furthermore, as a result of prolonged contact, Miller (2016) reports of the incorporation of Datooga (Nilotic) and Sukuma (Bantu) into the kinship terms of Hadzabe (Khoisan/Isolate). Likewise, Lusekelo (2019) found that prolonged contact yielded the incorporation of kinship terms from Sukuma (Bantu) into Datooga (Nilotic) in north-western Tanzania. The adaptation of forms of address due to colonization, westernization and urbanisation happened amongst the Shona in the city of Harare (Zimbabwe) (Mashiri 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as a result of prolonged contact, Miller (2016) reports of the incorporation of Datooga (Nilotic) and Sukuma (Bantu) into the kinship terms of Hadzabe (Khoisan/Isolate). Likewise, Lusekelo (2019) found that prolonged contact yielded the incorporation of kinship terms from Sukuma (Bantu) into Datooga (Nilotic) in north-western Tanzania. The adaptation of forms of address due to colonization, westernization and urbanisation happened amongst the Shona in the city of Harare (Zimbabwe) (Mashiri 2003).…”
Section: Introductionmentioning
confidence: 99%